2000
DOI: 10.1016/s0006-3495(00)76415-0
|View full text |Cite
|
Sign up to set email alerts
|

Actin Dynamics at the Living Cell Submembrane Imaged by Total Internal Reflection Fluorescence Photobleaching

Abstract: Although reversible chemistry is crucial to dynamical processes in living cells, relatively little is known about relevant chemical kinetic rates in vivo. Total internal reflection/fluorescence recovery after photobleaching (TIR/FRAP), an established technique previously demonstrated to measure reversible biomolecular kinetic rates at surfaces in vitro, is extended here to measure reversible biomolecular kinetic rates of actin at the cytofacial (subplasma membrane) surface of living cells. For the first time, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(57 citation statements)
references
References 29 publications
3
54
0
Order By: Relevance
“…Measurements of the actin dynamics in cultured smooth muscle cells (30) showed that actin kinetic parameters display a cell-wide gradient. The unbinding rate of actin near the plasma membrane at the cell-substrate contact regions, as measured using total internal reflection microscopy and fluorescence recovery after bleaching, was found to be spatially nonuniform throughout the cell (30). In some cell regions actin kinetics was fast, whereas in other regions it was slower.…”
Section: Traction Maps Of Single Smooth Muscle Cellsmentioning
confidence: 99%
“…Measurements of the actin dynamics in cultured smooth muscle cells (30) showed that actin kinetic parameters display a cell-wide gradient. The unbinding rate of actin near the plasma membrane at the cell-substrate contact regions, as measured using total internal reflection microscopy and fluorescence recovery after bleaching, was found to be spatially nonuniform throughout the cell (30). In some cell regions actin kinetics was fast, whereas in other regions it was slower.…”
Section: Traction Maps Of Single Smooth Muscle Cellsmentioning
confidence: 99%
“…To visualize F-actin, cells were microinjected with X-Rhodamine-labeled actin either alone or together with the inhibitory mDia2 antibody. To assay F-actin dynamics in the ventral cortex of cells, we used total internal reflection fluorescence recovery after photobleaching (TIR-FRAP) (Sund and Axelrod, 2000). FRAP of fluorescent actin in the ventral cell cortex using TIRF microscopy allows quantification of the rate and completion of fluorescence recovery, indicating how quickly fluorescent actin in the cortex cycles between the cytoskeleton-bound and cytoplasmic pools.…”
Section: Introductionmentioning
confidence: 99%
“…However, it should be taken into account that in comparison with conventional fluorescence microscopy, TIRFM signals are by about a factor 100 lower and need very sensitive optical detection systems in order to obtain good signal-to-noise ratios. TIRFM has been first described in 1981 (14), and since that time has been used increasingly for measuring cell-substrate contacts (15)(16)(17), membrane or protein dynamics (18), membrane proximal ion fluxes (19) as well as endocytosis or exocytosis (20)(21)(22).…”
mentioning
confidence: 99%